2019
DOI: 10.3390/atmos10050242
|View full text |Cite
|
Sign up to set email alerts
|

Sprinkler Irrigation Is Effective in Reducing Nitrous Oxide Emissions from a Potato Field in an Arid Region: A Two-Year Field Experiment

Abstract: In arid and semi-arid regions, water-saving irrigation is the primary mode of local agricultural production. Since the chemical fertilizer is the principal source of nitrous oxide (N 2 O) emissions, we present results from a two-year (2016-2017) field experiment on a potato field to verify the general influence of water-saving irrigation on N 2 O emissions. A split-plot experiment was established with two irrigation systems and two fertilizer treatments, which give a total of four treatments. Two different irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Aside from lowered irrigation rate as a cause for decreased N 2 O emissions [68,81]; decrease in N 2 O emissions can also be caused by soil aeration [84], though aeration effects on N 2 O production is highly dependent on soil moisture content [96], where microbial nitrification is then water-limited under arid conditions instead of O 2 -limited. Finally, water delivery was recently demonstrated to also contribute to differences in N 2 O emissions from irrigated fields [97]. By comparing flood irrigation to sprinkler and drip irrigation, researchers determined that the hydrologic forms (irrigation or flooding frequency, timing, and duration) will cause contrasting GHG emission patterns [98].…”
Section: N 2 O Emissions and Irrigation Treatmentsmentioning
confidence: 99%
“…Aside from lowered irrigation rate as a cause for decreased N 2 O emissions [68,81]; decrease in N 2 O emissions can also be caused by soil aeration [84], though aeration effects on N 2 O production is highly dependent on soil moisture content [96], where microbial nitrification is then water-limited under arid conditions instead of O 2 -limited. Finally, water delivery was recently demonstrated to also contribute to differences in N 2 O emissions from irrigated fields [97]. By comparing flood irrigation to sprinkler and drip irrigation, researchers determined that the hydrologic forms (irrigation or flooding frequency, timing, and duration) will cause contrasting GHG emission patterns [98].…”
Section: N 2 O Emissions and Irrigation Treatmentsmentioning
confidence: 99%
“…Due to the soil moisture status during summer months, N 2 O emissions in our experiment could thus be compared to studies where crops are irrigated. For example, Yang et al (2019) and Wang et al (2016) found that overhead sprinkler irrigation or surface drip irrigation, respectively, relative to flood irrigation, significantly reduced N 2 O emissions, which primarily wetted the soil surface and did not fill soil macropores in lower soil depths.…”
Section: Drought Obscured Treatment Effect On Ghg Emissionsmentioning
confidence: 99%
“…The surface layer in a field irrigated by sprinkler irrigation (SI) is relatively loose compared to FI. Therefore, in such soils, the NO 3 -N and NH 4 -N ions are less leached and remain more concentrated in the root zone [ 106 , 107 ], which makes them more easily absorbed by plant roots and, therefore, less prone to be turned into N 2 O [ 107 , 108 ]. SI is a water-saving approach, and soil conditions during SI, as well as drip irrigation (DI), favor NF in both cases.…”
Section: Management Options To Mitigate N 2 O Emis...mentioning
confidence: 99%